Green Management Efforts At Malaysian Federal Seaports: Contributor To The Core Competitiveness - Beleya, Prashanth (2022)
Developed economies have been the leaders in seeking after the plan for future development. Malaysia’s desire of being a sea nodal point in the South East Asian district lies in the abilities of seeking after aggressive systems. This study infers the significance of green management at portside activities at Malaysian federal seaports by taking a gander at the difficulties and the reasons of seeking after the technique